NANOSILVER-ENABLED FOOD STORAGE CONTAINERS: A CASE STUDY IN SUSTAINABILITY - WESTERBAND MARTINEZ, EDWARD I. (My University, 2018)
This work presents a midpoint life cycle assessment (LCA) utilized in a cradle-to-grave analysis to compare the environmental and human health impacts of nano-scale silver (nAg) enabled polymer food storage containers with their conventional counterparts. The raw materials and manufacturing, usage, washing, and final disposal life cycle phases are considered. The washing phase has the greatest impact among all the life cycle phases due to the electricity usage, which in turn is associated to fossil fuel consumption at the power plant; the impact related to the nAg leaching from the container into the wash water during this phase is insignificant. The environmental impact of synthesizing nAg is mostly related to the use of silver nitrate which in turn is related to silver ore mining. The LCA demonstrates an increase in the overall environmental impact related to the integration of nAg particles in food storage containers compared to conventional food storage containers. Two experimental tests were performed to fill the current research gap related to the nAg leaching during the washing and disposal of nAg enabled polymer food storage containers. The dishwashing simulation test demonstrates that the total silver released after four washing cycles is a small fraction of the initial content embedded on the product and that only 5% of the release is in the form of nAg. The landfill simulating test indicates that the nAg-enabled food storage container is not considered toxic waste since the leaching silver concentration is below the federal standard for this heavy metal. An environmental cost-benefit analysis is performed in order to compare the tradeoffs between nAg enabled polymer food storage containers environmental implications and their food saving benefits. The results illustrate that in general the environmental impacts associated to the production of poultry, bread, rice, raspberry, milk and orange juice are significantly greater than the that related to the addition of nAg into the food storage container.
Keywords: environmental impact; food container; sustainability; life cycle assessment